MEDIATED ARABIC LANGUAGE LEARNING FOR HIGHER EDUCATION IN COVID-19 SITUATION - Wargadinata, Wildana; Maimunah, Iffat; Febriani, Suci Ramadhanti; Humaira, Luluk (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
The COVID-19 emergency situation has affected all citizens of the world, including Indonesia and also all non-formal and formal educational institutions, such as higher educations. The Learning Process in various educational units, including tertiary institutions, experienced a total change to the use of internet or online media. The present article examines the media and the Arabic learning process at the university in the COVID-19 pandemic situation. The COVID-19 pandemic situation changed the way of learning Arabic students at UIN Maulana Malik Ibrahim Malang from conventional offline learning to learning using internet media online. This research is a qualitative descriptive study. The data are obtained through observation, questionnaires distributed through Google forms, online interviews through social media, and documentation. The result shows that the majority of students use the WhatsApp application, and most of them study autonomously through online platforms. Besides, it reveals that the most popular learning material is video. To improve their language skills, students are more likely to have peer-discussion activities. The study discovered a shift in Arabic learning by students of UIN Maulana Malik Ibrahim Malang from personal to instrumental as a result of the current COVID-19 pandemic situation. In this case, there was a transformation in Arabic learning from a personal-cultural approach to an instrumental-functional approach. This research has implications regarding the ideal Arabic learning process in the conditions of the COVID-19 pandemic. The shift also took place in the degree of teachers' dependence towards dependence on technology during the pandemic situation.